The Effect of Differences in Company Life Cycle and Earning Power on Earnings Management - Nisa Khaerin Nova; Sugiono Poulus; Sony Devano (Budapest International Research and Critics University, 2022)
This study aims to examine the effect of various stages of the company's life cycle and earnings power on earnings management. This research is motivated by the occurrence of earnings management phenomena that are still carried out on the financial statements of companies in the world, especially in Indonesia which can have a negative impact because this practice can lead to misinformation received by investors. The population of this study are non-financial companies indexed by Indonesian sharia shares (IHS) listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The final sample in this study were 130 companies using purposive sampling method and using path analysis techniques. The research data was processed with the help of SPPS and LISREL. The results of the analysis show that company's life cycle and earning power are correlated, the company's life cycle directly and indirectly has a negative effect on earnings management, earnings power has a positive direct effect on earnings management, but indirectly through the company's life cycle. have a negative effect on earnings management. Suggestions for further research can be to conduct broader research by using a different approach on each variable and adding other variables such as company size.